The plasticity of root traits and their effects on crop yield and yield stability - Dongxue Zhao; Peter de Voil; Victor O. Sadras; Jairo A. Palta; Daniel Rodriguez (Plant and Soil, 2025)
Context Phenotypic plasticity can be a valuable adaptation strategy for coping with environmental heterogeneity. There is limited information on the plasticity of root traits and their effect on yield and yield stability. Objectives With a perspective of phenotypic plasticity, we focus on functional root traits associated to water uptake in field-grown sorghum to answer: (i) How do genetic (G), environmental (E) and management (M) factors and their interactions, affect the root traits? and (ii) How do root traits and their plasticity affect yield and yield stability? Methods A new high-throughput functional root phenotyping approach was used in G × E × M trials to quantify two root traits, maximum rooting depth (MxRD) and a root activity index (RAindex). Crop phenotypic plasticities were determined using the reaction norm method. Results The applied G × E × M treatments created plastic responses between the tested hybrids. There was a hierarchy of plasticities for the different traits studied i.e., grain number traits > root traits > grain weight traits. The plasticity of root traits was associated with the stability of grain yield traits. Hybrids with high root plasticity tend to have more stable grain numbers and grain weights. Conclusions There is valuable genetic diversity in the mean value and plasticity of root traits that could be used to match root phenotypes to target production environments. Our root phenotyping approach can be a valuable tool for understanding the dynamic interactions between root function, root architecture and yield traits in the field under variable environments.